Music and the silent film : contexts and case studies, 1895-1924 - Marks, Martin Miller (New York : Oxford University Press, 1997)
Most people's view of silent film music is of a pianist playing old scores while watching the flickering screen. This title shows that there was much more to silent films and that often it was planned from the start as an integral part of the film. The author argues that film scores are a major and vibrant part of 20th century music.
1 Film and Music: An Introduction to Research 3 -- 2 First Stages, Dimly Lit: Sources and Scores Prior to 1910 26 -- 3 Film Scores in America, 1910-14 62 -- 4 Breil's Score for The Birth of a Nation 109 -- 5 Erik Satie's Score for Entr'acte 167.
Revision of the author's thesis (doctoral)--Harvard University, 1990.
Includes bibliographical references (pages 221-294) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Silent film music -- History and criticism; Film muet, Musique de -- Histoire et critique; MUSIC -- Instruction & Study -- Theory; Silent film music; Filmmuziek; Stomme films; Electronic book; Criticism, interpretation, etc